Mechanism of Layer Formation during Gas Nitriding of Remelted Ledeburitic Surface Layers on Unalloyed Cast Irons - Anja Holst; Stefan Kante; Andreas Leineweber; Anja Buchwalder (Metals, 2023)
Unalloyed cast iron materials exhibit low tribological and corrosive resistance. In this respect, nitriding has a wide range of applications for steels. In the case of cast iron, the advantageous properties of nitrided layers are impaired by the presence of graphite. Electron beam remelting of cast iron surfaces prior to nitriding removes graphite. The homogeneous ledeburitic microstructure within the approx. 1 mm-thick remelted layer enables the formation of a dense compound layer during subsequent nitriding. The main objective of this study is to investigate the nitriding mechanism of unalloyed ledeburitic microstructures. Due to the complex relationships, investigations were carried out on both conventional ferritic and pearlitic cast irons and Fe-based model alloys containing one to four additional alloying elements, i.e., C, Si, Mn and Cu. The iron (carbo-)nitride composition (γ’, ε) of this compound layer depends on the gas nitriding conditions, the chemical composition of the substrates and the microstructural constituents. As a result, a schematic model of the nitriding mechanism is developed that includes the effects of the nitriding parameters and alloy composition on the phase composition of the nitriding layer. These findings enable targeted parameter selection and a further optimization of both the process and the properties.